Spatial matching of emergency shelters to the distribution of residents in the light of transport behaviours of evacuees during war: the case of Suwałki - Borowska-Stefańska, Marta; Goniewicz, Krzysztof; Grama, Vasile; Horňák, Marcel; Masierek, Edyta; Morar, Cezar; Pénzes, János; Rochovská, Alena; Turoboś, Filip; Wiśniewski, Szymon (European Spatial Research and Policy, 2024)
The aim of the article was the assessment of the spatial matching of existing shelters (supply) to the distribution of residents in Suwałki (demand), considering their declared transport behaviours while evacuating during war. The analysis was conducted based on the locations of existing emergency shelters using data on population distribution (registration data with building accuracy). Spatial alignment was determined using the P-Median problem and E2SFCA. In terms of establishing vehicular or pedestrian travel time, the Manhattan metric based on the urban road network model was utilised. A model of vehicle movement speed was then constructed, while a constant speed was assumed for pedestrian movement. Additionally, survey data on the transport behaviour of inhabitants of Suwałki in the case of war were conducted in 2023. The study concluded that the population residing within the city limits should evacuate on foot, and that prior training on the evacuation process is especially necessary for those who reside in less populated areas of the city. The analyses also showed that existing emergency shelters are overly dispersed, making management difficult for emergency services. Since the current capacity of emergency shelters is not sufficient for the number and distribution of inhabitants of Suwałki, the most practical significance of this article in this respect is to indicate to the authorities the optimal number and location for emergency shelters (to improve the evacuation process).